Convalescent patient-derived monoclonal antibodies targeting different epitopes of E protein confer protection against Zika virus in a neonatal mouse model. Issue 1 (1st January 2019) - Niu, Xuefeng; Zhao, Lingzhai; Qu, Linbing; Yao, Zhipeng; Zhang, Fan; Yan, Qihong; Zhang, Shengnan; Liang, Renshan; Chen, Peihai; Luo, Jia; Xu, Wei; Lv, Huibin; et al.
ABSTRACT: The Zika virus (ZIKV) outbreak and its link to microcephaly triggered a public health concern. To examine antibody response in a patient infected with ZIKV, we used single-cell PCR to clone 31 heavy and light chain-paired monoclonal antibodies (mAbs) that bind to ZIKV envelope (E) proteins isolated from memory B cells of a ZIKV-infected patient. Three mAbs (7B3, 1C11, and 6A6) that showed the most potent and broad neutralization activities against the African, Asian, and American strains were selected for further analysis. mAb 7B3 showed an IC50 value of 11.6 ng/mL against the circulating American strain GZ02. Epitope mapping revealed that mAbs 7B3 and 1C11 targeted residue K394 of the lateral ridge (LR) epitope of the EDIII domain, but 7B3 has a broader LR epitope footprint and recognizes residues T335, G337, E370, and N371 as well. mAb 6A6 recognized residues D67, K118, and K251 of the EDII domain. Interestingly, although the patient was seronegative for DENV infection, mAb 1C11, originating from the VH3-23 and VK1-5 germline pair, neutralized both ZIKV and DENV1. Administration of the mAbs 7B3, 1C11, and 6A6 protected neonatal SCID mice infected with a lethal dose of ZIKV. This study provides potential therapeutic antibody candidates and insights into the antibody response after ZIKV infection.